Seismic retrofit of gravity load designed RC buildings using external steel concentric bracing systems. (April 2020) - Formisano, A.; Massimilla, A.; Di Lorenzo, G.; Landolfo, R.
Highlights: The paper discusses the seismic vulnerability of existing RC buildings. The use of steel concentric bracing systems for seismic retrofitting is investigated. The building seismic performance is evaluated through three different models. The three building models are retrofitted with external bracing systems. The results show the importance of infills and the effectiveness of steel bracings. Abstract: This paper discusses the seismic vulnerability of Reinforced Concrete (RC) buildings designed to gravity loads only, which are representative of the Italian building stock mainly erected between '70s and '80s, and investigates the use of external steel concentric bracing systems to upgrade their seismic performance. A case study building has been selected and designed according to the codes and the current practice in force at the time of construction. The seismic performance has been evaluated through the so-called N2 method in the format of the Capacity Spectrum Method applied to three different models of the building, namely bare frame, full infilled frame and pilotis frame, to highlight the role of the infill walls arrangement. The three models have been retrofitted with the external bracing systems designed with an adopted rational methodology. The external arrangement of the bracing systems has been chosen in order to both minimize the impact on the existing building and avoid the local interaction between the RC structural elements and the steel bracings, as well as the additional loads on the existing foundations. The results have shown the strong role of the infills in the structural behaviour of the existing building and the efficiency of the external steel bracing systems as retrofitting technique of existing RC buildings.